A reflective commentary of teaching critical thinking of privacy and surveillance in UK higher education. Issue 1 (February 2017) - Lin, Yu-Wei
The importance of data literacy and the need of raising and improving it through formal educational channel or public engagement has repeatedly been flagged up in each of the past Economic and Social Research Council-funded Data-Psst! Seminar I attended in 2014–2016. There is a real demand for action taking. I took advantage of the knowledge I learned from the Data-Psst seminars and devised a module teaching Level 5 undergraduate media students about critical issues in today's data-centric digital society, including privacy and surveillance. In this article, I share how the class activities were devised and carried out, and how guided engagement with the current debate in privacy and surveillance were realised. I also draw on relevant pedagogical theories to discuss my educational approaches, student performance, the challenges of the project, and evaluate and reflect upon the outcomes. This report from the field provides fresh first-hand information about the data ethics of the younger public who are practising media arts and their behaviours and attitudes towards privacy and surveillance. This article shall open up the discussion about the role educators play in enriching public engagement with critical thinking about Big Data. The lessons learned can also contextualise the pedagogical implication of the recent scholarly research on Big Data and privacy, and provide a framework for constructing future collaborative or creative projects.